Dynamic suppression of likely distractor locations: Task-critical modulation. - Allenmark, Fredrik; Stanković, Miloš; Müller, Hermann J.; Shi, Zhuanghua (Visual Cognition)
When a distractor frequently appears in a certain region of a search display, it interferes less with performance, reflecting learned distractor suppression. While this effect is well established, it remains unknown whether this suppression is ongoing (tonic) or deactivated upon task completion (phasic). To address this, the present eye-tracking study examined the time course of distractor suppression. Participants searched for and compared two targets to determine whether to make a response or withhold responding ("No-go" trials). The No-go trials allowed observation of post-decision suppression via eye movements. Response-critical target features either remained present for the whole trial (Experiment 1) or were removed halfway through (Experiment 2). In Experiment 1, distractors in the frequent region were substantially less likely to attract eye movements, including after inspection of both targets. However, in Experiment 2, the post-target distractor-region effect disappeared when the response-critical information was removed, indicating that suppression operates phasically and flexibly.